Immediate and Postponed Results of Short-Course Chemotherapy Regimens Containing Bedaquiline in Tuberculosis Patients with Multiple Drug Resistance - P. N. Golubchikov; T. I. Petrenko; D. Yu. Schegertsov; E. P. Stepanova; I. I. Pravdina; I. Yu. Pershina (Туберкулез и болезни лёгких)
The objective: to evaluate immediate and postponed efficacy of MDR TB patients' treatment with short-course chemotherapy regimens.Subjects and Methods. Efficacy and safety of treatment with short-course chemotherapy were evaluated in 42 MDR TB patients.Results. 36 (85,7%) patients completed treatment successfully, 1 (2,4%) patient died of non-tuberculosis, and 5 (11,9%) patients defaulted from treatment. There were no such outcomes as treatment failure and died of TB. Over the 4-year follow-up period after successful treatment completion, tuberculosis relapse was detected in 1 (1,8%) patient. No adverse events that required chemotherapy discontinuation were reported, amendment of chemotherapy regimen was required in 7 (16,7%) patients.